Analisis Penerapan Akad Mudharabah Mutlaqah Pada Tabungan Mabrur Untuk Biaya Perjalanan Ibadah Haji (Studi Pada Bank Syariah Indonesia KCP Stabat) - Soffi, Soffi Ramadhana (Jurnal Ekonomi dan Keuangan Syariah, 2022)
The formulation of the problem in this study is how to apply the mudharabah mutlaqah contract to mabrur savings for the cost of the pilgrimage at Bank Syariah Indonesia KCP Stabat, how is the flow of account opening to closing mabrur savings accounts at Bank Syariah Indonesia KCP Stabat. This study aims to describe the results of the formulation of the problem mentioned above. This study uses a field research method with a qualitative method that emphasizes the aspect of in-depth understanding of a problem. Sources of data in this study came from primary data and secondary data obtained from observations, interviews and documentation. The results of the research conducted by the author, the authors formulate conclusions regarding the application of the mudharabah mutlaqah contract on mabrur savings Bank Syariah Indonesia KCP Stabat has carried out in accordance with Islamic law, it's just that there is a lack of socialization or explanation to customers who still do not understand about the existence of a mudharabah mutlaqah contract. in mabrur savings or even the existence of a ratio in the mudharabah muthlaqah contract that the customer does not know about.. In addition, the process of opening and closing BSI accounts has been very helpful, making it very easy for customers to realize their wish to get a Hajj portion number and continue to the ground holy.